VDRL, TPHA, immunoglobulin in aborted and multipart woman's in Baghdad governorate - Raad Khalil AL-Husseinei; Khamael Majeed Kadaem; Lamya Auwad AL-Janabi; Mun'im Mustafa Fathei (مجلة كلية الطب, 2007)
Background: Syphilis disease remain as a problem especially in developing countries. it can be detected by serological tests and the infection may affected the immunoglobulins concentration and may cause spontaneous abortion.